Elaborating Waqf Muaqqat on Scientific Discussion - Uula, Mimma Maripatul; Rusydiana, Aam Slamet (International Journal of Waqf, 2025)
Temporary waqf (waqf muaqqat) is one of the important innovations in Islamic social finance that offers flexibility in the use of assets without eliminating the basic principles of waqf. This research aims to map the development of academic studies on temporary waqf and identify the main themes and future research opportunities. The method used was a bibliometric study and meta-analysis of 23 Scopus indexed journal articles that discussed the topic of temporary waqf. The analysis was performed using VOSviewer software to map the relationships of keywords, authors, and research clusters. The results of the analysis show that the research on temporary waqf is concentrated in five main clusters, namely: (1) temporary waqf for sustainable development, (2) temporary family waqf model, (3) temporary cash waqf investment, (4) temporary cash waqf deposits in Islamic banking, and (5) temporary waqf for refugee and humanitarian financing. These findings confirm that temporary waqf has great potential as a medium-term financing instrument that is adaptive, inclusive, and in line with maqasid al-shariah. This research contributes to enriching the contemporary waqf literature by presenting a comprehensive research map and providing directions for policy development and further research related to the management of temporary waqf in the modern era.